2016
DOI: 10.1038/tp.2016.123
|View full text |Cite
|
Sign up to set email alerts
|

Voice analysis as an objective state marker in bipolar disorder

Abstract: Changes in speech have been suggested as sensitive and valid measures of depression and mania in bipolar disorder. The present study aimed at investigating (1) voice features collected during phone calls as objective markers of affective states in bipolar disorder and (2) if combining voice features with automatically generated objective smartphone data on behavioral activities (for example, number of text messages and phone calls per day) and electronic self-monitored data (mood) on illness activity would inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
192
2
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 191 publications
(216 citation statements)
references
References 44 publications
5
192
2
2
Order By: Relevance
“…Voice (Faurholt-Jepsen et al, 2016) and facial (Mone, 2015) analysis can be utilized to detect mood and psychiatric disturbances and has been used to diagnose Parkinson’s disease and heart disease (Maor et al, 2016), and can be used to differentiate simulated versus real pain (Bartlett et al, 2014). Eye tracking during behavioral tasks can identify individuals with mild cognitive impairment and predict future progression to Alzheimer’s disease (Zola et al, 2013).…”
Section: High Definition Preventionmentioning
confidence: 99%
“…Voice (Faurholt-Jepsen et al, 2016) and facial (Mone, 2015) analysis can be utilized to detect mood and psychiatric disturbances and has been used to diagnose Parkinson’s disease and heart disease (Maor et al, 2016), and can be used to differentiate simulated versus real pain (Bartlett et al, 2014). Eye tracking during behavioral tasks can identify individuals with mild cognitive impairment and predict future progression to Alzheimer’s disease (Zola et al, 2013).…”
Section: High Definition Preventionmentioning
confidence: 99%
“…Some pioneers are already exploring the detection of disease by analysing speech patterns in patients 25. For instance, depressive episodes can be marked by systematic changes in vocal pitch,26 and early identification of heart failure may be feasible by measuring vocal changes arising from oedema in the vocal folds and lungs 27…”
Section: What Might Be Possible?mentioning
confidence: 99%
“…Abdullah et al [9] reported that combining self-reported data with data from several smartphone sensors and communication patterns resulted in reliable prediction of Social Rhythm Metric, a clinically-validated marker of stability and rhythmicity for individuals with bipolar disorder. A different study [10] collected voice features that were automatically generated using smartphones from 28 outpatients on a daily basis during a period of 12 weeks.…”
Section: The Monitoring Of Activity Of Daily Living and Episodic Epismentioning
confidence: 99%